Pendugaan Status Trofik Dengan Pendekatan Kelimpahan Fitoplankton Dan Zooplankton Di Waduk Sengguruh, Karangkates, Lahor, Wlingi Raya Dan Wonorejo Jawa Timur. [Estimation Of Trophic Status Use Phytoplankton And Zooplankton Density Approachment At Sengguruh Dam, Karangkates, Labor, Wlingi Raya And Wonorejo Dam East Java] - Asus Maizar Suryanto H,; Herawati Umi S. (Jurnal Ilmiah Perikanan dan Kelautan, 2009)
Abstract The aim of these study was to know plankton (phytoplankton and zooplankton spesies and density at Sengguruh dam, Karangkates, Lahor, Wlingi Raya and Wonorejo, and to estimated trophic status these dams use phytoplankton and zooplankton density approachment. These study used descriptive methode with survey technic. Data wich is taken from each dam is taken from four different station that suggested the representated dam condition. The result showed according to the range phytoplankton density: at Karangkates between 144-236 ind/ml is clustered as oligotrophic, the range phytoplankton density at sengguruh between 217-313 ind/ml is clustered as oligotrophic. At Lahor dam between 5.35612.704 ind/ml is clustered as mesotrophic, at Wlingi Raya dam between 74-1480 ind/m' is clustered as mesotrophic to eutrophic, while at Wonorejo dam between 48-288 ind/ml is clustered as oligotrophic waters. According to the range zooplankton density: at Karangkates dam between 28.153-132.056 ind/lt is clustered as mesotrophic, Lahor dam between 4.996-14.275 ind/lt is clustered as mesotrophic, Wlingi Raya dam between 623-3.114 ind/lt is clustered as oligotrophic to mesotrophic, and Wonorejo dam between 2-6 ind/lt is clustered as mesotrophic. The differences of estimation result of trophic level at each dam according to phytoplankton and zcoplankton density data is showed that dam ecosystem was imbalance